New insights in Neanderthal palaeoecology using stable oxygen isotopes preserved in small mammals as palaeoclimatic tracers in Teixoneres Cave (Moià, northeastern Iberia) - Fernández-García, M. (2022)
The northeastern region of Iberia constitutes a natural pass-area for arriving populations into the peninsula and becomes a key area to understand Neanderthal resilience to changing environmental conditions experienced during Marine Isotope Stage 3 (MIS 3; 60-30 ka). Short-term but repeated occupations by Neanderthal groups occurred in Teixoneres Cave (Moia, Barcelona) in alternation with large and small carnivores during MIS3. Abundant small-mammal remains accumulated in units III and II of this fossiliferous deposit, providing local climatic and environmental information. This work focuses on the taphonomic history of small-mammal faunas, which a is clue to validate previous palaeoecological interpretations. As was observed with leporids and bird remains, raptors are considered the major source of small-mammal remains. The most likely accumulator is an opportunistic predator, the eagle owl, with very rare inputs by mammalian carnivores. In parallel, high-resolution palaeoclimatic data are provided through oxygen isotope analyses (delta O-18) of rodent teeth from four subunits (IIIb to IIa), which are compared with independent methods of palaeotemperature estimations. According to air temperatures estimated from delta O-18 rodent teeth, cooler conditions than present day (-1.6/- 0.5 degrees C) are recorded along the sequence, but homogenous (< 1 degrees C). Complementary methods also explain higher rainfall than present day (+44/+682 mm). Only slight changes between units III and II show climatic instability, which could be related to palimpsests of stadial-interstadial events. Climatic stable conditions are reported from coeval isotopic and palaeodiet analyses from northeastern Iberia in agreement with the palynological records that underline how the Mediterranean area could have sustained rich ecosystems that assured the Neanderthal subsistence during the abrupt climatic pulsations of the Late Glacial.